Is Islamic Finance, social finance? / Saadiah Mohamad - Mohamad, Saadiah (Faculty of Business and Management, 2014)
Developments in Islamic Finance and Social Finance and illustrate an increasing interest globally to look at alternative ways of financing and creating value in the society. Islamic Finance and Social Finance are emerging disciplines that challenge and influence the global finance industry and both have similar mandates in terms of their emphasis in ethical business and investment. Islamic Finance is governed by the rules of the shariah that prohibits riba or interest and gharar (uncertainty), sinful business sectors such as pornography and alcohol and unethical practices such as exessive speculation and gambling. These forms of restrictions are similar to the negative screening methodology adopted by the socially responsible investment or SRI which is a rising component of Social Finance.